Analyses of E3 Ubiquitin-Ligase Target Adapter-Encoding BTB Gene Families in Viridiplantae - Jacobson, Zachary; Gingerich, Derek J. (My University, 2018)
Ubiquitylation, the covalent attachment of the small protein ubiquitin (Ub), can modify the degradation, localization, or activity of target proteins and is crucial for proper organism function. This attachment is achieved by the sequential action of E1(Ub-activating), E2 (Ub-conjugating), and E3 (Ub-ligase) enzymes. The E3 complexes bind the target protein and facilitate attachment of the Ub moiety. There are multiple families of E3’s encoded in eukaryotic genomes; one of these are the CRL3 type. CRL3 E3 complexes consist of three proteins; a BTB (Bric-a-Brac, Tramtrack, Broad Complex) domain-containing protein, Cullin 3, and RBX1. The BTB proteins are the target-adapters, binding to the proteins to be ubiquitylated via motifs appended to the ~100 amino-acid BTB domain. Genes encoding BTB proteins have been identified in a wide range of eukaryotic organisms (including fungi, protists, animals, and plants) but the BTB gene families in different groups show great variability in size, complexity, and composition. In land plant genomes thus far studied, BTB gene families are large (~75-150 members) and complicated (with multiple subtypes based on the presence of a diverse set of target-binding motifs). We are interested in when the particular CRL3 family composition seen in the higher plants (as defined by the BTB target-adapter repertoire available) may have arisen in evolution.
Color poster with text, figures and tables.
Keywords: Viridiplantae; Ubiquitin-ligase; Posters